2014
DOI: 10.1016/j.yebeh.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Neurology Quality-of-Life (Neuro-QoL) measurement system in adult epilepsy

Abstract: Epilepsy is a chronic neurological disorder that results in recurring seizures and can have a significant adverse effect on health related quality of life (HRQL). Neuro-QoL is an NINDS-funded system of patient reported outcome measures for neurology clinical research, which was designed to provide a precise and standardized way to measure HRQL in epilepsy and other neurological disorders. Using mixed-methods and item response theory-based approaches, we developed generic item banks and targeted scales for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…Developed with senior citizens in mind. This measures in largely cognitive based and fails to tap into the emotional domain [59]International use: English and multiple other languages available [58]Cost: Free; must contact copyright owner to use [58]Administration: self [58]Estimated completion time: < 10 minutes [58]Response options: 7-point Likert scale [58]NeuroQoL16 domains(564)Physical, emotional, cognitive and social patient functionValidity : + in studies of neurological populations and pediatric TBI population and + content validity in military populations with TBI [4, 48, 61, 63]Reliability: + in studies of neurological populations and pediatric TBI population + internal consistency in military population with TBI [48, 60]Measure can be used for adults and children; however, this may not take into consideration the unique challenges of an older adult. NeuroQol considered at item bank in which the assessment is individually tailored based on responses to previous items.…”
Section: Resultsmentioning
confidence: 99%
“…Developed with senior citizens in mind. This measures in largely cognitive based and fails to tap into the emotional domain [59]International use: English and multiple other languages available [58]Cost: Free; must contact copyright owner to use [58]Administration: self [58]Estimated completion time: < 10 minutes [58]Response options: 7-point Likert scale [58]NeuroQoL16 domains(564)Physical, emotional, cognitive and social patient functionValidity : + in studies of neurological populations and pediatric TBI population and + content validity in military populations with TBI [4, 48, 61, 63]Reliability: + in studies of neurological populations and pediatric TBI population + internal consistency in military population with TBI [48, 60]Measure can be used for adults and children; however, this may not take into consideration the unique challenges of an older adult. NeuroQol considered at item bank in which the assessment is individually tailored based on responses to previous items.…”
Section: Resultsmentioning
confidence: 99%
“…The Neuro-QoL system has been validated in adult epilepsy, and individual Neuro-QoL measures have been validated in other diseases. [20][21][22]…”
Section: Neuro-qolmentioning
confidence: 99%
“…Increased knowledge of patients about epilepsy and the presence of positive attitudes towards epilepsy were associated with decreased stigma scores in patients with epilepsy (32,33). Victorson et al reported that the T-score was 49.7 ± 9.1 in adult epilepsy patients by using the Neuro-QoL stigma scale (34). In the Neuro-QoL user manual, the T-score was defined as 50.6 ± 6.7 for epilepsy (16).…”
Section: Discussionmentioning
confidence: 99%